Analysis Of Mapping The Potential Of The Creative Economy In Bintan Regency During The Covid-19 - Lamidi Lamidi (Syntax Idea, 2022)
The Creative Economy is one of the economic activities that have an essential meaning in supporting the financial resilience of the people of Bintan Regency, developing innovation, creativity, and competitiveness, realizing economic growth, and creating job opportunities in Bintan Regency. The purpose of this study is to analyze several potentials during the COVID-19 pandemic in the Creative Economy sector in Bintan Regency, which prioritizes the Need for Human Resources and Natural Resources that have the opportunity to be appropriately managed. The research method used is descriptive qualitative with a case study approach in Bintan Regency. Secondary data regarding the Creative Economy are collected and subsequently studied in depth. The findings show that the Creative Economy in Bintan Regency is in bad condition. Due to the prevalence of tourism activities that attract tourists as targets for expanding the Creative Economy in border regions with neighboring nations, it has become identified that there is neither a strong appeal nor a substantial market. In addition, there is a need to strengthen capital and identify potential, lay the economic base, and support future policies for the Creative Economy during the COVID-19 pandemic in Bintan Regency.